Implementasi Metode Design Thinking dalam Tata Panggung Teater Karma Gadis Bisu Karya NS - Mega Sheli Bastiani (Institut Seni Indonesia Yogyakarta, 2022)
Implementation Design Thinking Method in the Stage Arrangement of the Karma Gadis Bisu Theater by NS.The design thinking method is a method that is commonly used in the world of design, especially interior design, product design, and visual communication design. Design thinking adopts the way of thinking of a designer in carrying out his creative process. It can be said that design thinking is a method of thinking/perspective/point of view in doing something. This design aims to develop knowledge through the implementation of design thinking methods into the realism of theater stage design. The design process using this method uses 5 stages, Discovery, Interpretation, Ideation, Experimentation, and Evolution, and taking the object of the Karma Gadis Bisu script by NS. The results of this design are in the form of a qualitative concept of theater stage design data. Meanwhile, according to data searches on the scopus.com website, a theater stage layout design using this creative method has not been found. Therefore, this design is feasible to be continued.Keywords: design thinking method, stage sets, theater, Karma Gadis Bisu